(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To determine the antimicrobial resistance status of Klebsiella pneumoniae in patients with bloodstream infection (BSI) and the appropriateness between empiric antibiotic selection and antimicrobial susceptibility testing results. Materials and methods: A cross-sectional descriptive study was conducted on 31 patients diagnosed with bloodstream infection caused by K. pneumoniae and treated at the Department of Infectious Diseases, Hai Duong General Hospital from January 1, 2023 to September 30, 2025. Results: Results: ESBL-producing K. pneumoniae isolates accounted for 38.7%. High resistance rates were observed to penicillin antibiotics (63.7–89%); the cephalosporin group (22.6–38.7%); quinolones (15.4–26.7%); aminoglycosides (4–22%); and carbapenems (3.2–6.5%). One case showed intermediate resistance to colistin. The rate of multidrug-resistant (MDR) strains was 45.2%. No extensively drug-resistant or pan-drug-resistant strains were identified. Empiric antibiotics selected for patients with suspected bloodstream infection potentially related to Klebsiella pneumoniae included cephalosporins (38.7%), fluoroquinolones (41.9%), the amikacin group (12.9%), and carbapenems (9.6%). The corresponding antimicrobial resistance results reported on the antimicrobial susceptibility testing were 38.7%, 36.7%, 35.7%, and 3.2%, respectively. Conclusion: Klebsiella pneumoniae showed low susceptibility to most tested antibiotics, and many empirically selected antibiotics used in treatment were found to be resistant